Stabilization of heavy metals in municipal sewage sludge by freeze–thaw treatment with a blend of diatomite, FeSO4, and Ca(OH)2. (3rd August 2017) - Wang, Jing; Fu, Rongbing; Xu, Zhen
ABSTRACT: In this work, the effects of diatomite with 15% FeSO4 7H2 O and 7.5% Ca(OH)2 on sludge stabilization were investigated using batch leaching tests. The influence of cell rupture caused by freezing and thawing on stabilization was also evaluated. The results indicated that the optimal diatomite percentage was 2%. Cell rupture by freezing and thawing reduced heavy metal leachability, followed by cell death and decrease of organic groups. The concentration of heavy metals in sludge leachate increased after cell rupture, indicating that the heavy metal leachability was reduced after freezing and thawings. Moreover, the stabilization effects were generally improved after freezing and thawing. As compared with the stabilization of the original sludge, the unstable fractions decreased and the residual fractions of the heavy metals increased in the stabilized sludge after cell rupture. Implications : This study developed a method to stabilize heavy metals in municipal sewage sludge. Diatomite combined with FeSO4 ·7H2 O and Ca(OH)2 improved the treatment of sewage sludge contaminated by heavy metals. Cell lysis by freeze–thaw treatment reduced the risk of leaching heavy metals caused by cell death and decreased major organic groups in the sludge.